Strategic approach of Analyzen for the consumers to find a reason to upgrade from a regular base product to a premium product - Haider, Sirzil (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.